Long-term risk of degenerative spinal diseases following osteoporosis: A South Korean nationwide cohort study - Handol Jung; Shin Won Kwon; Hyung Jin Shin; Sunho Kim; Chanhee Shin; Taekyung Jin; Hohyun Jung; Youngoh Bae; Sung Hwan Hwang (Journal of Back and Musculoskeletal Rehabilitation, 2026)
Background Osteoporosis (OP) is a systemic skeletal disorder characterized by reduced bone density and microarchitectural deterioration, leading not only to fragility fractures but also to progressive spinal deformities. Recent evidence suggests that OP may contribute to degenerative spinal diseases (DSDs), yet longitudinal data remain limited. Objective This study aimed to evaluate the long-term risk and temporal relationship between newly diagnosed OP and subsequent development of major DSD subtypes using a nationwide population-based cohort. Methods A retrospective cohort study was conducted by utilizing data from the Korean National Health Insurance Service (NHIS) between 2002 and 2013. Newly diagnosed OP cases were identified and matched 1:10 using propensity score matching. Outcomes included four major DSD subtypes—intervertebral disc disorders, spinal stenosis, spondylosis, and spondylolisthesis—identified using claims-based ICD-10 codes. Incidence rate ratios (IRRs) were calculated, and multivariable Cox proportional hazards models were applied to estimate adjusted hazard ratios (aHRs), controlling for demographic and clinical covariates. A 3-year washout period and up to 9 years of follow-up were implemented. Results Among over one million participants, both osteoporosis groups—with and without pathological fractures—showed significantly elevated IRRs and aHRs for all major DSD subtypes compared with matched controls. The risk elevation was pronounced and sustained in OP patients without pathological fractures. Conclusion OP was independently associated with an increased long-term risk of DSDs, including among patients without pathological fractures. These findings underscore the need for early risk stratification and proactive spinal health management in patients with OP to mitigate the growing burden of spine disorders in aging populations.